PSV-B-26 Performance of sunflower protein meal and dried yeast as secondary protein sources in feline diets. (8th October 2021) - Brewer, Lauren; Panasevich, Matthew; Frantz, Nolan; Daristotle, Leighann
Abstract: The objectives of this study were to assess graded inclusions of sunflower protein meal (SPM; crude protein: 54%, crude fat: 11%, crude fiber: 4%) and dried yeast (DY; crude protein: 50%, crude fat: 3%, crude fiber: 2%) on nutrient digestibility, stool quality, and palatability in adult cats. Both SPM and DY were included at 5% and 10% in replacement of pea protein in a high-protein, chicken-based feline diet to maintain equal macronutrient concentrations across all test diets (formulated to 41% crude protein, 18% crude fat, 3% crude fiber). The study was approved and followed by the facility's Institutional Animal Care and Use Committee. A standard 2-bowl palatability test over a 2-day period was executed with adult cats (n = 30 each) to determine intake ratios between test diets (5% and 10% SPM or 5% and 10% DY), and test diets vs. control. Total tract nutrient digestibility was evaluated (n = 8 per diet) with 5 days of diet acclimation followed by 5 days of total fecal collection. Stool quality was evaluated on a 1–5 scale, where 1 = hard/formed and 5 = non-formed/diarrhea. All data were analyzed by ANOVA (SAS v9.4) and T-tests post-hoc (Minitab 18). Palatability and stool quality were similar (P > 0.05) between all diets. Protein digestibility was lower for DY-containing diets, compared with control (5% DY at P = 0.0083 and 10% DY at P = 0.0336), but not significantly different for SPM diets (P > 0.05). However, average protein digestibility was >88% across all diets. The alternative protein sources tested showed merit for inclusion to diversify ingredient sources while maintaining palatability in cat diets.